(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The first examples of practical ethics are proverbs and proverbs written on clay tablets in cuneiform, the world’s first writing, three and a half thousand years ago. Samaritan proverbs and sayings are also noteworthy; many of them have risen to the level of universal wisdom and are still used in the East in a slightly different form. In addition, various moral problems are raised in the epic "Gilgamesh". When talking about ancient Greek ethics, it is customary to mention the names of four great philosophers; Socrates, Plato, Aristotle, Epicurus. But in fact, even before them, a lot of work on ethics was done in Ancient Greece